2016
DOI: 10.1108/jiabr-07-2013-0023
|View full text |Cite
|
Sign up to set email alerts
|

Discovering perceptions of Muslim consumers toward the ICRIC Halal logo

Abstract: Purpose The purpose of this study is to explore the perceptions of Muslim consumers on the Islamic Chamber Research & Information Center (ICRIC) Halal logo. In particular, the paper evaluates the main messages of the logo and describes the organization’s characteristics behind this logo. Design/methodology/approach This exploratory research conducts a semi-structured interview with visual aids method to identify the Malay Muslim’s perceptions toward the ICRIC Halal logo. Findings Results of the study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…This cluster was termed “concerned.” It seems that this group of consumers is concerned about halal food authenticity since the halal logo is generally regarded as the main identifier of halal food authenticity. In fact, some authors have argued that the halal logo represents “an important source of information that eliminates doubt in the minds of consumers” (Borzooei & Asgari, 2016). Figure 8 shows the major topics detected within each cluster using the LDA method.…”
Section: Resultsmentioning
confidence: 99%
“…This cluster was termed “concerned.” It seems that this group of consumers is concerned about halal food authenticity since the halal logo is generally regarded as the main identifier of halal food authenticity. In fact, some authors have argued that the halal logo represents “an important source of information that eliminates doubt in the minds of consumers” (Borzooei & Asgari, 2016). Figure 8 shows the major topics detected within each cluster using the LDA method.…”
Section: Resultsmentioning
confidence: 99%
“…The halal logo is one of the important elements that represent the lawfulness of a product's production, trade and ingredient factors (Hussain et al, 2016). The halal logo is an essential source of information that removes uncertainty in the thoughts of consumers (Borzooei and Asgari, 2016). The halal logo is used as a mechanism to determine the "halalness" of food products, which is generally invisible to consumers (Marzuki et al, 2012).…”
Section: Halal Logomentioning
confidence: 99%
“…That is why there are several studies concentrated on the halal logo (e.g. Bonne and Verbeke, 2008;Borzooei and Asgari, 2016;Hussain et al, 2016;Shafie and Othman, 2006;Wibowo and Ahmad, 2016). A study conducted by Ghadikolaei (2016) was found that the halal logo has a positive influence on consumers purchase intention among the Muslim and non-Muslim consumers.…”
Section: Halal Logomentioning
confidence: 99%
“…Supported by the Jewish community, at the time involved in the creation of a novel certification system defined as "kosher" and based on a strict set of dietary rules called "kashrut", the Muslim specialists designed their first Halal logo. Soon after, an ever-increasing amount of Halal certification bodies (more than one hundred on a global scale) [68,69], as well as a rising number of regulation and standards (e.g., Standards and Metrology Institute for Islamic Countries, Organization of Islamic Cooperation) spread, specifically in food commodities such as meat and meat-based products, taking care of different countrywide or domestic Muslim protocols (e.g., Sunni, Shia) or responding to diverting Muslim divisions (e.g., Hanafi, Hanbali, Maliki) [68]. Then, a variety of Halal logos and certificates became widespread in the Halal markets, increasing the heterogeneity in certification procedures (e.g., lack of uniformity) and generating confusion and misunderstandings from one certificate to another, as well as from one country to another [70,71].…”
Section: Halal Certificationmentioning
confidence: 99%
“…For instance, Algeria has created a unique national collective brand owned by the Algerian Standardization Institute (IANOR, Algeria), developed on the basis of the Organization of Islamic Cooperation (OIC, Kingdom of Saudi Arabia) standards and on the Standards and Metrology Institute for Islamic Countries (SMIIC, Turkey). Such an approach has been adopted to enhance the Algerian economy through the creation of a Halal national trademark, as well as to increase the international recognition of Algerian companies in "explaining the halalness" of their products [69]. On the contrary, non-Muslim countries such the United States of America and Australia encompass approximately 14 and 24 authorized certifying bodies, respectively, illustrating how the interest in centralizing the certification of Halal products in a single body mostly belongs to Islamic countries.…”
Section: Halal Certificationmentioning
confidence: 99%